Citra Destinasi sebagai Strategi Peningkatan Jumlah Wisatawan Danau Toba "Monaco of Asia" di Kabupaten Samosir - Hengki Mangiring Parulian Simarmata; Roy Sahputra Saragih (Journal of Education, Humaniora and Social Sciences (JEHSS), 2020)
Lake Toba is one of the priority tourism destinations which has natural, cultural, and spiritual wealth. In realizing Lake Toba as the Monaco of Asia, it is necessary to pay attention to various aspects, one of which is the tourism image of Lake Toba in the eyes of tourists. The increase of destination image is influenced by the trust of tourists in tourist objects. This study aims to determine how the influence of destination image on tourist visit decisions in Samosir Regency. The sample used in this study were 100 tourists who were visiting in Samosir Regency. This research is descriptive and quantitative research. Data collection techniques using observation and distribution of questionnaires to tourists. The sampling technique was random sampling with a simple linear regression analysis. The results showed that destination image has a significant positive effect on tourist visits. Where the coefficient of determination (R2) is 0.258, which means that destination image has an influence of 25.8% on the decision to visit tourists to Lake Toba, Samosir Regency, while the remaining 74.2% is influenced by other factors not examined in this study such, covid-19 condition, service quality, tourism performance. and others.